2018
DOI: 10.3126/jcmc.v8i3.23748
|View full text |Cite
|
Sign up to set email alerts
|

Health care seeking behaviours of mother having under 24 months old child attending Outpatient Department of Tribhuvan University Teaching Hospital, Kathmandu

Abstract: Health care seeking behaviour of a mother has an important role in reducing morbidity and mortality related common childhood illness amongst under-five children. The main objective of this study was to identify the health care seeking behaviour of mothers who attended tertiary level hospital in Kathmandu for common childhood illness. The study was conducted in the paediatrics out-patient department of Tribhuvan University Teaching Hospital Kathmandu by employing a descriptive design under the quantitative rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These findings of the study supported by previous study conducted on Teaching hospital, Kathmandu, Nepal by which revealed that that about 1/3 rd (33.3%) of the respondents did not seek health care facility due to far distance. 14 Moreover, present study exhibits that there is significant association between health seeking behavior of community people with marital status (p=0.002), occupation (p=0.001), level of education (p=0.030), source of income (p<0.001), and monthly income (p=0.006), duration of illness (p=0.008) and availability of nearest health care services (p<0.001). These findings of the study are parallel to the previous study conducted in Dharan on senior citizen showed that there is significant relationship between health seeking behavior with source of income (p= 0.003) and monthly income (p=0.001).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…These findings of the study supported by previous study conducted on Teaching hospital, Kathmandu, Nepal by which revealed that that about 1/3 rd (33.3%) of the respondents did not seek health care facility due to far distance. 14 Moreover, present study exhibits that there is significant association between health seeking behavior of community people with marital status (p=0.002), occupation (p=0.001), level of education (p=0.030), source of income (p<0.001), and monthly income (p=0.006), duration of illness (p=0.008) and availability of nearest health care services (p<0.001). These findings of the study are parallel to the previous study conducted in Dharan on senior citizen showed that there is significant relationship between health seeking behavior with source of income (p= 0.003) and monthly income (p=0.001).…”
Section: Resultsmentioning
confidence: 57%
“…13 These findings are also similar to the study conducted on a mother having 24 months' children in outpatient department of teaching hospital Kathmandu where most of the respondents (90.6%) seek help for their health problem first time from the modern medication. 14 and study conducted in Chitwan Bharatpur also revealed that 83.7% of the respondents seek help from modern medication. 15 Likewise study conducted by Ali and Woldearegai (2019) in Afar pastoral community shows that majority of the respondents (71%) prefer modern medicine.…”
Section: Methodsmentioning
confidence: 94%